Managing Multicultural Education in the Merdeka Curriculum: Strategies, Challenges, and Insights - Reskia, Dewi; Kaharuddin, Kaharuddin; Wardah, A. Ria (International Journal of Asian Education, 2025)
Multicultural education fosters inclusivity, social cohesion, and mutual respect in diverse societies. Indonesia’s Merdeka Curriculum provides a flexible, student-centered framework, making it a strategic platform for integrating multicultural education. This study examines the implementation, challenges, and institutional support for multicultural education within the Merdeka Curriculum, focusing on how schools manage diversity in teaching and learning. Data were collected through semi-structured interviews, classroom observations, and document analysis in selected junior high schools using a qualitative case study approach. Findings reveal inconsistent implementation due to teacher preparedness gaps, resource limitations, and resistance to change. While some schools integrate multicultural content effectively through inclusive teaching practices and extracurricular programs, others struggle due to inadequate teacher training and a lack of culturally diverse materials. Institutional support is critical, as schools with structured policies and administrative backing demonstrate more effective multicultural education practices. This study underscores the need for targeted teacher training, the development of multicultural learning resources, and stronger institutional policies. Addressing these challenges will enhance cultural inclusivity, student engagement, and cross-cultural understanding in Indonesian education. Future research should explore long-term impacts and best practices for sustaining multicultural education within the evolving Merdeka Curriculum.